Mapping the Literature on influence of Market Orientation & Marketing Practices on the Performance of SMEs: A Bibliometric review - Muluk, Sonal; Pahurkar, Dr. Rajesh (The journal of contemporary issues in business and government, 2022)
The focus of this research is to provide a critical analysis of the marketing orientation and marketing practices in small and medium-sized businesses (SMEs). Bibliometric review is selected for the study to understand the most significant countries engaging in the marketing orientation research between 1996 and 2022. This study includes 474 papers from Scopus listed journals during stated time. Study focuses on the citations and publication details of the articles and research papers based on marketing orientation and marketing practices in SMEs. In this study a Bibliometrix, an open source ‘R’ software used as a mapping and visualization tool to perform intricate bibliometric analyses. It has been observed that maximum research papers are published with Journal of Small Business Management and Journal of Business Research. Research author Gilmore A and O’Dwyer M has published maximum documents 11 and 10 respectively. It has been observed that after 2012 till 2020 more number of publications done in this area.